Type 2 diabetes mellitus with chronic kidney disease benefits from long-term restriction of dietary protein intake: a 10-year retrospective cohort study - Danfeng Liu; Qiuling Li; Runli Jia; Weiting He; Xuan Zhao; Mengting Pan; Xiaojie Chen; Yanhui Wang; Yaxi Zhu; Hanchen Hou; Jianteng Xie; Wenjian Wang (BMC Nutrition)
Abstract Objective This study aimed to investigate the relationship between long-term dietary protein intake (DPI) restriction and clinical outcomes in patients with type 2 diabetes mellitus (T2DM) and chronic kidney disease (CKD). Methods We conducted a retrospective study in both T2DM with CKD cohort from eight centers, with a follow-up period from January 2014 to September 2023 and the National Health and Nutrition Examination Survey (NHANES) dataset. DPI was evaluated based on the serum urea creatinine ratio (sUCR). The primary outcomes included initiation of dialysis, progression to end-stage renal disease, renal transplant, serum creatinine doubling, cardiovascular and cerebrovascular diseases. Results In the T2DM with CKD cohort, 820 patients were selected from a total of 856 and categorized into three groups, propensity score matching at a 1:1:1 ratio, according to their DPIsUCR levels. The median follow-up time was 32.94 months. Patients on a restricted protein diet (DPIsUCR ≤ 1.0 g/kg·d) showed improved prognosis and delayed progression to primary endpoints. In CKD stages 3–4, patients with DPIsUCR < 0.8 g/kg·d exhibited significantly improves prognosis. Similarly, in the NHANES cohort, 1723 patients were classified into 3 groups, with a median follow-up time of 87.19 months. A restricted protein diet (DPIsUCR ≤ 1.0 g/kg·d) markedly improved prognosis and reduced mortality. Conclusion Our data provide the strong evidence that T2DM patients with CKD benefits from long-term restriction of DPIsUCR ≤ 1.0 g/kg·d by improving composite endpoints. In T2DM patients with CKD at stages 3–4, an intensive restriction of DPIsUCR (< 0.8 g/kg·d) significantly improved composite endpoint. Clinical trial number Not applicable.